Estruturas de confinamento de baixa dimensionalidade em superfícies de hélio líquido suspensas - Dantas, Davi Soares (2012)
The system of electrons on liquid helium (EoH) is one of the most ideal objects for investigating the fundamental principles of the physics of low dimensionality, since they do not have the inhomogeneities and impurities generally found on semiconductors. Besisdes, these systems are expected to have future technological applications as quantum bits, which are of fundamental importance as building blocks of future quantum computers. Usually, the low-dimensional confinements structures for EoH suggested in the literature are based on a planar surface, where the lateral confinement is induced by an external potential controlled by electrodes. In this work, we suggest an alternative way to produce lateral confinement in liquid helium surfaces, namely, we demonstrate that the shape of the surface can be designed to produce single and double quantum dots by adjusting the shape of a cavity in the substrate. The surface was calculated for four different shapes of substrate cavity: i) a cilyndrical cavity, generating a single quantum dot; ii) a ring-shaped cavity, generating a quantum ring; iii) two cubic cavities connected by a channel, creating a coupled double-dot structure; and iv) two channel-shaped cavities that intersect perpendicularly to each other, where a single dot is formed in the intersection point. The electron is then deposited and confined to move on each surface by an external electric field. Our results show that the electron energy levels in these systems can be tuned by varying the electric field and the bulk level, which are easily adjustably. The effect of an external magnetic field on the energy spectrum in one of these systems is also investigated.